Parsing cognitive and emotional empathy deficits for negative and positive stimuli in frontotemporal dementia. (January 2015) - Oliver, Lindsay D.; Mitchell, Derek G.V.; Dziobek, Isabel; MacKinley, Julia; Coleman, Kristy; Rankin, Katherine P.; Finger, Elizabeth C.
Abstract: Objectives: Behavioural variant frontotemporal dementia (bvFTD) is a debilitating neurodegenerative disorder characterized by frontal and temporal lobe atrophy primarily affecting social cognition and emotion, including loss of empathy. Many consider empathy to be a multidimensional construct, including cognitive empathy (the ability to adopt and understand another's perspective) and emotional empathy (the capacity to share another's emotional experience). Cognitive and emotional empathy deficits have been associated with bvFTD; however, little is known regarding the performance of patients with bvFTD on behavioural measures of emotional empathy, and whether empathic responses differ for negative versus positive stimuli. Methods: 24 patients with bvFTD and 24 healthy controls completed the Multifaceted Empathy Test (MET; Dziobek et al., 2008 ), a performance-based task that taps both cognitive and emotional facets of empathy, and allows for the discrimination of responses to negative versus positive realistic images. MET scores were also compared with caregiver ratings of patient behaviour on the Interpersonal Reactivity Index, which assesses patients' everyday demonstrations of perspective taking and empathic concern. Results: Patients with bvFTD were less accurate than controls at inferring mental states for negative and positive stimuli. They also demonstrated lower levels of shared emotional experience, more positive emotional reactions, and diminished arousal to negative social stimuli relative to controls. Patients showed reduced emotional reactions to negative non-social stimuli as well. Lastly, the MET and IRI measures of emotional empathy were found to be significantly correlated within the bvFTD group. Conclusions: The results suggest that patients with bvFTD show a global deficit in cognitive empathy, and deficient emotional empathy for negative, but not positive, experiences. Further, a generalized emotional processing impairment for negative stimuli was observed, which could contribute to the emotional empathy deficit. This work highlights potential treatment targets and a means to assess the impact of novel therapies on socioemotional impairment in bvFTD. Highlights: The performance-based Multifaceted Empathy Test was used to assess empathy in bvFTD. bvFTD associated with a cognitive empathy deficit for negative and positive states. Patients with bvFTD showed deficient emotional empathy for negative stimuli. Performance-based empathy measure was correlated with caregiver reports of empathy.